Layer-By-Layer Fabrication of Thicker and Larger Human Cardiac Muscle Patches for Cardiac Repair in Mice - Wang, Lu; Zhang, Jianyi (Frontiers in Cardiovascular Medicine, 2022)
The engineered myocardial tissues produced via most manufacturing techniques are typically just a few dozen micrometers thick, which is too thin for therapeutic applications in patients. Here, we used a modified layer-by-layer (LBL) fabrication protocol to generate thick human cardiac muscle patches (hCMPs) with thicknesses of ~3.75 mm. The LBL-hCMPs were composed of a layer of endothelial cells (ECs) sandwiched between two layers of cardiomyocytes (CMs): both cell populations were differentiated from the same human induced pluripotent stem cell line (hiPSCs) and suspended in a fibrin matrix, and the individual layers were sutured together, leaving channels that allowed the culture medium to access the internal cell layer. The LBL-hCMPs were cultured on a dynamic culture platform with electrical stimulation, and when compared to Control-hCMPs consisting of the same total number of hiPSC-ECs and -CMs suspended in a single layer of fibrin, hiPSC-CMs in the LBL-hCMPs were qualitatively more mature with significantly longer sarcomeres and expressed significantly higher levels of mRNA transcripts for proteins that participate in cardiomyocyte contractile activity and calcium handing. Apoptotic cells were also less common in LBL- than in Control-hCMPs. The thickness of fabricated LBL-hCMP gradually decreased to 0.8 mm by day 28 in dynamic culture. When the hCMP constructs were compared in a mouse model of myocardial infarction, the LBL-hCMPs were associated with significantly better measurements of engraftment, cardiac function, infarct size, hypertrophy, and vascularity. Collectively these observations indicate that our modified LBL fabrication protocol produced thicker hCMPs with no decline in cell viability, and that LBL-hCMPs were more potent than Control-hCMPs for promoting myocardial repair in mice.